Cognitive—Motor Interference in an Ecologically Valid Street Crossing Scenario - Janouch, Christin; Drescher, Uwe; Wechsler, Konstantin; Haeger, Mathias; Bock, Otmar; Voelcker-Rehage, Claudia (Frontiers in Psychology, 2018)
Laboratory-based research revealed that gait involves higher cognitive processes, leading to performance impairments when executed with a concurrent loading task. Deficits are especially pronounced in older adults. Theoretical approaches like the multiple resource model high-light the role of task similarity and associated attention distribution problems. It has been shown that in cases where these distribution problems are perceived relevant to participant’s risk of falls, older adults prioritize gait and posture over the concurrent loading task. Here we investigate whether findings on task similarity and task prioritization can be transferred to an ecologically valid scenario. Sixty-three younger adults (20 - 30 years of age) and 61 older adults (65 – 75 years of age) participated in a virtual street crossing simulation. The participants’ task was to identify suitable gaps that would allow them to cross a simulated two way street safely. Therefore, participants walked on a manual treadmill that transferred their forward motion to forward displacements in a virtual city. The task was presented as a single task (crossing only) and as a multitask. In the multitask condition participants were asked, among others, to type in three digit numbers that were presented either visually or auditorily. We found that for both age groups, street crossing as well as typing performance suffered under multitasking conditions. Impairments were especially pronounced for older adults (e.g. longer crossing initiation phase, more missed opportunities). However, younger and older adults didn’t differ in the speed and success rate of crossing. Further, deficits were stronger in the visual compared to the auditory task modality for most parameters. Our findings conform to earlier studies that found an age-related decline in multitasking per-formance in less realistic scenarios. However, task similarity effects were inconsistent and questions the validity of the multiple resource model within ecologically valid scenarios.